Analysis of Challenges and Barriers to the Integration of a Promotional Mix in Tlocor Marine Tourism Sidoarjo - Agustina Nikmatus Solichah; Sheidy Yudhiasta (Indonesian Journal Publisher, 2026)
Tlocor Marine Tourism in Sidoarjo Regency, East Java, offers significant potential through its coastal scenery, mangrove ecotourism, boat trips to Lusi Island, and the local fishing community. Despite these attractions, the site remains underrecognized due to limited and inconsistent promotional efforts. This study analyzes the challenges and barriers in implementing the promotional mix at Tlocor Marine Tourism. A qualitative descriptive approach was used, collecting data through in-depth semi-structured interviews with managers, community members, and government officials, supplemented by field observations and documentation. Findings reveal that while the five elements of the promotional mix advertising, sales promotion, personal selling, public relations, and direct marketing are applied, they are neither integrated nor consistent. Digital advertising, particularly via social media, is sporadic and reaches a limited audience; sales promotions are restricted to discounts; personal selling lacks standard procedures and systematic training; public relations efforts are reactive; and direct marketing has ceased due to past misuse of visitor databases. Key barriers include post-pandemic human resource shortages, budget constraints, psychological trauma from prior database misuse, and bureaucratic obstacles regarding land ownership and legal permits. These factors hinder the establishment of a structured and sustainable promotional strategy. The study concludes that leveraging Tlocor Marine Tourism’s potential requires strategic planning, enhanced training, consistent digital engagement, and administrative support to overcome operational, financial, and regulatory challenges. Addressing these barriers will help attract a broader audience, improve visitor experience, and support sustainable tourism development. This study provides practical insights for local tourism managers and policymakers to enhance promotional strategies and optimize tourism development.